2018
DOI: 10.3151/jact.16.306
|View full text |Cite
|
Sign up to set email alerts
|

Cement Hydration Rate of Ordinarily and Internally Cured Concretes

Abstract: In the present paper, adiabatic temperature rise test was used to evaluate the effect of internal curing on cement hydration rate and final degree of hydration in normal and high strength concretes. In the experiments, emphases were placed on the impacts of internal curing and water to cementitious material ratio on the adiabatic temperature rise characteristics. Two kinds of concrete, ordinarily cured concrete and internally cured concrete were used in the experiments. In each kind, four concrete mixtures wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The porosity and pore structure of concrete are closely related to the water–cement ratio ( W / C ) and the degree of hydration ( α ) [ 30 ]. It has been reported that the degree of hydration can reach as high as 0.89 when the W / C is 0.3 [ 31 ]. The increase in porosity leads to a decrease in concrete compactness, making it easier for chloride ions to penetrate into the concrete.…”
Section: Models and Numerical Simulationsmentioning
confidence: 99%
“…The porosity and pore structure of concrete are closely related to the water–cement ratio ( W / C ) and the degree of hydration ( α ) [ 30 ]. It has been reported that the degree of hydration can reach as high as 0.89 when the W / C is 0.3 [ 31 ]. The increase in porosity leads to a decrease in concrete compactness, making it easier for chloride ions to penetrate into the concrete.…”
Section: Models and Numerical Simulationsmentioning
confidence: 99%
“…Changing the actual age of adiabatic temperature rise test into the equivalent age according to the temperature history, the degree of cement hydration obtained by Eq. ( 3) can be fitted as below (Pane and Hansen 2002;Zhang et al 2009;Wang et al 2018).…”
Section: Steel Formmentioning
confidence: 99%
“…Cement hydration parameters of each concrete determined by the adiabatic temperature rise tests and the mineral compositions of the concrete, along with density, specific heat, elastic modulus, and compressive strength of each concrete, are listed in Table 4. Details regarding the adiabatic temperature rise tests of the three concretes can be found in a previous publication (Wang et al 2018). Figure 4 displays a comparison of the degree of cement hydration and equivalent age diagrams between test results and the model prediction [Eq.…”
Section: Input Parameters For Model Calculationmentioning
confidence: 99%
“…Likewise, it was implemented the calorimeter designed to perform heat of hydration measurements on cement paste samples. The novelty of this work is to display that the calorimeter was developed using concurrent design (optimization algorithms) unlike existing calorimeters implemented [13][14][15][16]. It is expected that this work will be one of the first to develop optimized calorimeters for cement mixtures [17].…”
Section: Introductionmentioning
confidence: 99%